Measuring Student Satisfaction with Academic Applications at BINUS University Through the Customer Satisfaction Score (CSAT) Framework - Mario Fransisco (Bina Nusantara University, 2026)
This study examines student satisfaction with four key academic applications used at BINUS University: BinusMaya, Neksus Semester Plan, Thesis App, and the Library App which play a central role in supporting learning activities, academic administration, and access to academic resources. The study applies the Customer Satisfaction Score (CSAT) framework, a widely used approach for evaluating user satisfaction with system quality, usability, and performance. The CSAT evaluation is adapted to the functional characteristics of each application. Thesis App, BinusMaya, and Neksus Semester Plan, which directly support core academic processes, are assessed using four dimensions: fulfilment, efficiency, system availability, and accuracy. Meanwhile, the Library App, which functions as a supporting academic resource platform, is evaluated using ease of use, features and functionality, and system performance. A quantitative descriptive approach was employed, with data collected through an online survey conducted between July and September 2025. A four-point Likert scale was used to encourage clear evaluative responses, and the sample size was determined using Slovin’s formula. The findings indicate that students generally report positive satisfaction across all applications. Thesis App performs strongly in terms of efficiency and accuracy, while the BinusMaya shows high satisfaction in fulfilment. Neksus Semester Plan receives favourable evaluations in efficiency but faces responsiveness challenges during peak usage periods. Library app is positively rated for its features, although improvements are needed in system performance and interface consistency. Overall, the results suggest that BINUS University’s academic applications effectively support student activities, while also highlighting the importance of continuous system improvement.